β-receptor blocker enhances anti-tumor immunity via inhibiting lactate-induced norepinephrine metabolism of macrophages during malignant pleural effusion - Zhang, Ru; Wang, Weijia; Li, Aitian; Wang, Huishang; Liu, Xiaoyan; Fan, Feifei; Wang, Ying; Zhang, Huanyu; Chang, Jingxia; Zhang, Yinyin; Wang, Hongmin; Miao, Lijun; et al. (Frontiers in Immunology, 2025)
IntroductionMalignant pleural effusion (MPE) is associated with poor quality of life and mortality in patients with tumors. In clinical practice, we observed that patients with malignant pleural effusion (MPE) and concurrent heart disease exhibited a decrease in MPE volumes following treatment with β-receptor blockers for heart disease. Immunosuppressive tumor microenvironment was found to play a substantial role in the progression of MPE, and mainly attributed to tumor-associated macrophages (TAMs). However, whether β-receptor blockers improve MPE through affecting the immune microenvironment especially TAMs and the potential mechanism behind remains unclear.MethodsIn this study, we collected the MPE samples from MPE and heart disease patients treated with propranolol, and performed flow cytometry experiment to evaluate the effect of propranolol on MPE immune microenvironment. Then, the mechanism that how propranolol effectively reprogrammed the immunosuppressive microenvironment of MPE was conducted by the experiments of mass spectrometry, RNA-seq, flow cytometry, immunofluorescence, western blotting, etc. Lastly, to further evaluate the effect of propranolol on MPE therapy in vivo, we developed a mouse model of MPE. We administrated propranolol into MPE-bearing mice to investigate the therapy efficacy and the changes of MPE microenvironment by the experiments of computed tomography (CT) scanning, flow cytometry, etc.ResultsWe observed that propranolol treatment in MPE patients with heart disease decreased TAM frequency and immunosuppression and enhanced anti-tumor immunity. Macrophages in MPE exhibited an immunosuppressive phenotype via the activation of norepinephrine metabolism. Subsequently, we found that lactate was increased in MPE and may contribute to an increase in TAM frequency and inhibition of anti-tumor immunity by macrophages. Additionally, lactate triggered phenylalanine/norepinephrine signaling and further induced macrophage immunosuppression in an ERK-depended way. Lastly, in the MPE mouse model, propranolol inhibited MPE development and reversed the immune microenvironment of MPE.DiscussionHere, we reveal the mechanism by which lactate induces macrophage immunosuppression via activating phenylalanine/norepinephrine signaling. Our findings highlight that blocking norepinephrine signaling by β-receptor blockers is an attractive therapeutic strategy to enhance anti-tumor immunity in the context of MPE